Hydraulic fracturing and the Crooked Lake Sequences: Insights gleaned from regional seismic networks. Issue 8 (23rd April 2015) - Schultz, Ryan; Stern, Virginia; Novakovic, Mark; Atkinson, Gail; Gu, Yu Jeffrey
Abstract Within central Alberta, Canada, a new sequence of earthquakes has been recognized as of 1 December 2013 in a region of previous seismic quiescence near Crooked Lake, ~30 km west of the town of Fox Creek. We utilize a cross‐correlation detection algorithm to detect more than 160 events to the end of 2014, which is temporally distinguished into five subsequences. This observation is corroborated by the uniqueness of waveforms clustered by subsequence. The Crooked Lake Sequences have come under scrutiny due to its strong temporal correlation (>99.99%) to the timing of hydraulic fracturing operations in the Duvernay Formation. We assert that individual subsequences are related to fracturing stimulation and, despite adverse initial station geometry, double‐difference techniques allow us to spatially relate each cluster back to a unique horizontal well. Overall, we find that seismicity in the Crooked Lake Sequences is consistent with first‐order observations of hydraulic fracturing induced seismicity.